Combustion Synthesis of Ca2Si5N8: Eu2+ Phosphors and their Luminescent properties. Issue 7 (2nd May 2013) - Chung, Shyan‐Lung; Chou, Wei‐Chi; Heo, J.
<x xml:space="preserve">Abstract</x> A combustion synthesis method has been developed for synthesis of Eu2+‐doped Ca2Si5N8 phosphor and its photoluminescence properties were investigated. Ca, Si, and Eu2O3 powders were used as the Ca, Si, and Eu sources. NaN3 and NH4Cl were found necessary to be added for the formation of the product phase and addition of Si3N4 was found to enhance the product yield. These powders were mixed and pressed into a compact, which was then wrapped up with an igniting agent (Mg + Fe3O4). The reactant compact was ignited by electrical heating under a N2 pressure of 0.7 MPa. Effects of these experimental parameters on the product yield were investigated and a reaction mechanism was proposed. The synthesized Ca2Si5N8: Eu2+ phosphor absorbs light in the region of 300–520 nm and shows a broad band emission in the region of 500–670 nm due to the 4f65d1 → 4f7 transition of Eu2+. Eu2O3 was found partially unreacted and a certain amount of oxygen is believed to be incorporated into the lattice of the product phase. The peak emission intensity (~93% of a commercially available phosphor, YAG:Ce3+v) and the peak emission wavelength (571–581 nm) were found to be lower and shorter, respectively, than that reported in the literature. These are considered to be mainly due to oxygen incorporation, which not only reduces nephelauxetic effect and crystal field splitting but also causes a lowering of internal quantum efficiency.